Health Related Studyability-An Approach to Structure Health Promotion Interventions at Universities - Mona Kellner; Klaus Weiß; Janina Gassert; Gerhard Huber (Frontiers Media S.A., 2021)
So far, the only existing prerequisite to enter an academic institution is a specific diploma, like a high school diploma, or another comparable certified document. Other requirements may only be a numerus clausus for certain fields of study to pave the bureaucratic way for a prospective student into their university life. The way first year students dive into their first academic experiences is entirely left to themselves. (Soft) Skills and Competences that exceed the expertise of the chosen courses but are essential for this new, and very challenging, chapter of their lives are not taught to them. Therefore, student health promotion for young adults is essential to build and sustain a healthy lifestyle during their academic careers. Nevertheless, it is important to consider not only a student's perspective but also structural and organizational conditions within the academic institutions. The further development of Ilmarinen's concept of workability may help to construct a theoretical and empirically based concept to implement health-promoting conditions for a student health promotion system at universities. Ilmarinen's concept was chosen by the work group in terms of the structure, which may be adapted to a university since it can be seen as a student's workplace.